Anticoagulation Resumption in a Patient With Mechanical Heart Valves, Antithrombin Deficiency, and Hemorrhagic Transformation Following Thrombectomy After Ischemic Stroke - Li, Yi-Chen; Wang, Rong; Xu, Hang; Ding, Lan-Ping; Ge, Wei-Hong (Frontiers in Pharmacology, 2020)
Anticoagulation is essential for patients undergoing mechanical heart valve replacement; however, the timing to re-initiate the anticoagulant could be a dilemma that imposes increased risk for bleeding events in patients suffering from the life-threatening hemorrhagic transformation after ischemic stroke. Such a situation was presented in this case report. A 71-year-old woman was transferred directly to the Neurocritical Care Unit because hemorrhagic transformation occurred following the mechanical thrombectomy for ischemic stroke. Since she had a history of prosthetic metallic valve replacement, it was carefully evaluated how the anticoagulating therapy could balance the hemorrhagic and thrombotic risks. On day 6 after the onset of hemorrhage transformation, the laboratory results of coagulation and fibrinolysis strongly suggested thrombosis as well as antithrombin deficiency. The short-acting and titratable anticoagulant argatroban was immediately initiated at low dose, and thrombosis was temporarily terminated. On day 3 of anticoagulation resumption, argatroban was discontinued for one dose when PT and APTT significantly prolonged after argatroban infusion. Aortic valve thrombosis was detected the next day. The anticoagulation was then strengthened by dose adjustment to keep mitral valve intact, to stabilize the aortic valve thrombosis, and to decrease the aortic flow rate. The intravenous argatroban was transited to oral warfarin before the patient was discharged. This study is the first report of administering argatroban and titrating to its appropriate dose in the patient with valve thrombosis, antithrombin deficiency and hemorrhagic transformation after mechanical thrombectomy for acute ischemic stroke. Notably, the fluctuations argatroban brings to the coagulation test results might not be interpreted as increased bleeding risk. This case also suggested that the reported timing (day 6 to day 14 after hemorrhage) of anticoagulant resumption in primary intracerebral hemorrhage with mechanical valves might be late for some patients with hemorrhagic transformation.